Comparison of fungal communities and nonvolatile flavor components in black Huangjiu formed using different inoculation fermentation methods - Li, Pingping; Su, Rui; Wang, Qi; Liu, Kunyi; Yang, Hai; Du, Wei; Li, Zhengang; Chen, Song; Xu, Bin; Yang, Wen (Frontiers in Microbiology, 2022)
Black Huangjiu (BH) is a traditional alcoholic beverage in China, which is very popular among people. BH, fermented using different methods (simultaneous inoculation, sequential inoculation), was used to investigate different methods on changes in the composition of fungal communities and nonvolatile flavor compounds (nVFCs) by high-throughput sequencing (HTS) and ultraperformance liquid chromatography - tandem mass spectrometer (UPLC-MS/MS). The results showed that Rhizopus and Saccharomyces were the predominant fungal genera throughout fermentation, and 471 nVFCs were detected in BH after fermentation. Compared to that observed simultaneous inoculation, Rhizopus increased at the end of sequential fermentation, and the contents of the organic acids and their derivatives increased significantly [variable importance in the projection (VIP) > 1.0, P < 0.05, fold change (FC) > 2], while the contents of lipids and lipid-like molecules decreased significantly (VIP > 1.0, P < 0.05, FC < 0.5). Through the correlation analysis of 32 nVFCs with significant differences (VIP > 1.0, P < 0.05, FC >32 or < 0.03) and the community, it was found that lipids and lipid-like molecules (12), organic acids and derivatives (10) were significantly (P < 0.05) negatively correlated with Saccharomyces, and were significantly (P < 0.05) positively correlated with Rhizopus. Compared with simultaneous inoculation, BH fermented by sequential inoculation, the taste was stronger, sweeter, mellow and softer. Our findings provide information on nVFC dynamics and will aid in the selection of beneficial strains to improve BH quality.